HUBUNGAN KETERAMPILAN MEMBACA PEMAHAMAN DAN KETERAMPILAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 6 PADANG - Gulo, Rika Zuwita; Abdurahman, Abdurahman; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT                                                                                         The purpose of this study are describe (1) the ability of reading comprehension class X students of SMA Negeri 6 Padang, (2) the ability to write essays arguing class X students of  SMANegeri 6 Padang, and (3) the correlation between of reading comprehension skills and the ability to write an essay arguing class X students of SMA Negeri 6 Padang. The data in this study were collected by using an objective test and a performance test. The result of the study are (1) the ability of reading comprehension class X students of SMA Negeri 6 Padang are in more than enough qualification with the average value 71.04, (2) the ability to write essays arguing class X students of SMA Negeri 6 Padang are more than enough to qualify with the average value 75.81, (3) there was a significant correlation between of reading comprehension skills with the ability to write an argument essay class X SMA Negeri 6 Padang because based on the t-test, the alternative hypothesis (H1) is accepted at 95% significance level and degrees of freedom n-1 with t count> t table, which is 7.37> 1.70.            Kata kunci: membaca pemahaman, menulis karangan argumentasi